Prognostic factors and survivals of children with steroid-resistant nephrotic syndrome - Partini Pudjiastuti Trihono; Nina Dwi Putri; Aman B Pulungan (Paediatrica Indonesiana, 2013)
Background Children with steroid resistant nephrotic syndrome(SRNS) generally survive, although during the course of diseasetheir kidney function may decrease, leading to end-stage renaldisease (ESRD). There have been few studies reporting on thesurvivals of children with SRNS.Objectives To determine patient and kidney survival rates in childrenwith SRNS at the first, second, third, fourth, and fifth years; and toevaluate the effects of age at onset, initial kidney function, hypertension,and type of resistance, on the survivals of children with SRNS.Methods This retrospective cohort study was performed usingsecondary data obtained from medical records of patients with SRNS inDepartment of Child Health, Cipto Mangunkusumo Hospira~ between2004-2011. The outcomes of kidney survivals were defined in two ways:lack of doubling of base creatinine levels and lack of ESRD.Results There were 45 children with SRNS in our study. Their medianduration ofillness was 24 (range 12-95) months. Twenty percent of thesubjects died, 31.1 % had a doublingofbase creatinine levels, and 13.4%developed ESRD. Life survival rates of subjects at the first, second,third, fourth, and fifth years after diagnosis were 93 %, 84%, 80"/ri, 7 2%,and 61 %, respectively. Kidney survival rates determined by the lackof doubling of base creatinine levels at the first, second, third, fourthand fifth years were 92%, 72%, 56%, 42%, and 34%, respectively, whilekidney survival rates determined by the lack ofESRD were 97%, 88%,81 %, 70"/o, and 58%, respectively. Age at onset, initial kidney function,hypertension at onset, and type of resistance, did not significantly affectthe survivals of children with SRNS.Conclusion Children with SRNS are prone to develop a doublingof base creatinine levels and ESRD. Factors such as age, initialkidney function, hypertension at onset, and type ofresistance, donot significantly affect both, life and kidney survivals of childrenwith SRNS.